PENGARUH LATIHAN SLALOM DRIBBLE TERHADAP KETERAMPILAN MENGGIRING BOLA PADA TIM SEPAKBOLA SMK TARUNA YAYASAN MANDIRI - Safitri, Nur?aini; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is aims to discover if there are any effect of the dribbling skills of SMK Taruna Yayasan Mandiri Pekanbaru, as so that can help the dribbling skills put to its maximum efforts to achieve the desired maximum result. This research is an experimental research, and the population in this research is the football team SMK Taruna Yayasan Mandiri Pekanbaru, and the sample in this research are the whole population of the team that are consists of 15 people. The instrument that has been done to determine the dribbling skills in this research is the dribble test. Following that, the data is processed with statistics, to test the normality with the liliefors test on the significant level (). The hypothesis that are proposed is the effects of slalom dribble exercise on resulting T analysis resulting Tcount 5,660 and Ttable 1,761, that concludes that Tcount > Ttable Based on the analysis of statistic data, it showed the average of the pretest of 0,134 and the average of posttest 0,139, then the data is considered normal. Thus, the effects of the slalom dribble exersice on dribbling skill improvement on SMK Taruna Yayasan Pekanbaru can be seen.Key words : Slalom dribble, Dribbling skills